The Auctioning of a Failing Firm - Lars Persson (The Research Institute of Industrial Economics (IUI), 1998)
This paper evaluates the welfare consequences of the failing firm doctrine in the EU and US merger laws. I combine an oligopoly model with an 'endogenous valuations' auction model. Thereby, I take into account that, in an oligopoly, a firm's willingness to pay for the assets depends on the identity of the alternative buyer. The main result is that the doctrine leads to cost inefficiencies, due to a 'least danger to competition' (LDC) condition, which favors small, and thus inefficient, firms. In particular, the LDC condition implies that small firms can preempt acquisitions that would lead to both higher producer surplus and higher consumer surplus.
Keywords: K21; L13; L41; 330; Competition policy; Failing firm defense; Auction; Fusion; Wettbewerbsrecht; Insolvenz; Fusionskontrolle; Auktionstheorie; Theorie